Acquisition of Coinfection and Simultaneous Transmission of Borrelia burgdorferi and Ehrlichia phagocytophila by Ixodes scapularis Ticks - Levin, Michael L. (American Society for Microbiology, 2000)
The agents of Lyme disease (Borrelia burgdorferi) and human granulocytic ehrlichiosis (Ehrlichia phagocytophila) are both transmitted by the tick Ixodes scapularis. In nature, ticks are often infected with both agents simultaneously. We studied whether previous infection with either Borrelia or Ehrlichia in ticks would affect acquisition and transmission of a second pathogen. Ehrlichia-infected I. scapularis nymphs were fed upon Borrelia-infected mice, and Borrelia-infected I. scapularis nymphs were fed upon Ehrlichia-infected mice. The efficiency with which previously infected nymphal ticks acquired a second pathogen from infected hosts was compared to that of uninfected ticks. An average of 51% ± 15% of ticks acquired Ehrlichia from infected mice regardless of their prior infection status with Borrelia. An average of 85% ± 10% of ticks acquired Borrelia from infected mice regardless of their prior infection status with Ehrlichia. Also, we assessed the efficiency with which individual nymphs could transmit either agent alone, or both agents simultaneously, to individual susceptible hosts. An average of 76% ± 9% of Borrelia-infected ticks and 84% ± 10% of Ehrlichia-infected ticks transmitted these agents to mice regardless of the presence of the other pathogen. There was no evidence of interaction between the agents of Lyme disease and human granulocytic ehrlichiosis in I. scapularis ticks. The presence of either agent in the ticks did not affect acquisition of the other agent from an infected host. Transmission of the agents of Lyme disease and human granulocytic ehrlichiosis by individual ticks was equally efficient and independent. Dually infected ticks transmitted each pathogen to susceptible hosts as efficiently as ticks infected with only one pathogen.